Unmet needs for healthcare and social support services in patients with Huntington's disease: a cross-sectional population-based study. Issue 1 (December 2015) - van Walsem, Marleen; Howe, Emilie; Iversen, Kristin; Frich, Jan; Andelic, Nada
Abstract Background In order to plan and improve provision of comprehensive care in Huntington's disease (HD), it is critical to understand the gaps in healthcare and social support services provided to HD patients. Research has described utilization of healthcare services in HD in Europe, however, studies systematically examining needs for healthcare services and social support are lacking. This study aims to identify the level and type of met and unmet needs for health and social care services among patients with HD, and explore associated clinical and socio-demographic factors. Methods Eighty-six patients with a clinical diagnosis of HD living in the South-Eastern region of Norway were recruited. Socio-demographic and clinical characteristics were collected. The Needs and Provision Complexity Scale (NPCS) was used to assess the patients' needs for healthcare and social services. Functional ability and disease stage was assessed using the UHDRS Functional assessment scales. In order to investigate factors determining the level of total unmet needs and the level of unmet needs for Health and personal care and Social care and support services, multivariate logistic regression models were used. Results A high level of unmet needs for health and personal care and social support services were found across all five disease stages, but most marked in disease stage III. The middle phase (disease stage III) and advanced phase (disease stages IV and V) of HD increased odds of having a high level of total unmet needs by 3.5 times and 1.4 times respectively, compared with the early phase (disease stages I and II). Similar results were found for level of unmet needs in the domain Health and personal care. Higher education tended to decrease odds of high level of unmet needs in this domain (OR = 0.48) and increase odds of higher level of unmet needs in the domain of Social care and support (OR = 1.3). Patients reporting needs on their own tended to decrease odds of having unmet needs in Health and personal care (OR = 0.57). Conclusions Needs for healthcare and social services in patients with HD should be assessed in a systematic manner, in order to provide adequate comprehensive care during the course of disease.